2006
DOI: 10.1121/1.4786679
|View full text |Cite
|
Sign up to set email alerts
|

Aural classification of impulsive-source active sonar echoes

Abstract: The goal of this effort is to develop automatic target classification technology for active sonar systems by exploiting knowledge of signal processing methods and human auditory processing. Using impulsive-source active sonar data, formal listening experiments were conducted to determine if and how human subjects can discriminate between sonar target and clutter echoes using aural cues alone. Both trained sonar operators and naive listeners at APL-UW were examined to determine a baseline performance level. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Not only does this allow for correlating with the entire space, but it also removes any error induced by the MDS analysis. We also observe that the listener similarity matrix 8 is a perceptual equivalent to matrices used in kernel methods for regression and classification such as kernel-based PCA [ 1] and Support Vector Machines [ 12].…”
Section: B Kernel Matchingmentioning
confidence: 94%
See 3 more Smart Citations
“…Not only does this allow for correlating with the entire space, but it also removes any error induced by the MDS analysis. We also observe that the listener similarity matrix 8 is a perceptual equivalent to matrices used in kernel methods for regression and classification such as kernel-based PCA [ 1] and Support Vector Machines [ 12].…”
Section: B Kernel Matchingmentioning
confidence: 94%
“…Since the auditory system relies on time-frequency-like decomposition, and sonar echoes are transient in nature, we demonstrate this approach using features ofthe form (2) gh(x) = h(t, f)Sx (t, f) t,f where S, (t, f) is the envelope of the output of a PattersonHoldsworth auditory filter bank [10] and h(t, f) is a timefrequency weighting function. For this class of signal features, it can be shown that the optimal weighting function according to Equation 1 is…”
Section: New Feature Identificationmentioning
confidence: 99%
See 2 more Smart Citations
“…There is anecdotal evidence and mounting experimental evidence 3,4 to suggest that when auditioned ͑i.e., auralized or listened to͒ by a human operator explosive-source echoes from man-made metallic objects sound very different than similar echoes from naturally occurring objects. This paper describes the development of an automatic classifier for explosive-source active sonar based upon the specific aural cues or perceptual signal features employed in the human auditory system.…”
Section: Introductionmentioning
confidence: 98%